Disease burden of influenza in Spain: A five-season study (2015–2020) - Iván Sanz-Muñoz; Irene Arroyo-Hernantes; Alejandro Martín-Toribio; Marina Toquero-Asensio; Javier Sánchez-Martínez; Carla Rodríguez-Crespo; Silvia Rojo-Rello; Marta Domínguez-Gil; Marta Hernández-Pérez; Eduardo Tamayo; Ruth Gil-Prieto; Ángel Gil-de-Miguel; et al. (Human Vaccines & Immunotherapeutics)
Influenza accounts for 30% of the total morbidity and mortality in the European Union. However, the specific burden in different European countries is largely unknown, and more research is needed to ascertain the reality of this disease. In this retrospective study, we analyzed the burdens of hospitalization, intensive care unit (ICU) admission and in-hospital mortality in Spain over five seasons (2015–2020) via publicly available Minimum Basic Datasets (MDBS). The data revealed that influenza had a major impact in Spain, with approximately 29,000 hospitalizations, 2,200 ICU admissions, and 1,600 deaths each season. In this period, approximately 7.8% of those hospitalized required ICU admission, and 5.7% died in the hospital due to influenza, with wide differences in these parameters depending on the season due to the virological characteristics of the major circulating viruses. More than 60% of those hospitalized were over 65 years of age, and approximately 82% of those who died were elderly, demonstrating that the greatest burden of hospitalization and mortality is centered on this age group. The annual direct cost of influenza was approximately €128 million per season, with more than 80% of this cost centered on people over 45 years of age.